Frequency of Completely Immunize Children According to Expanded Program on Immunization (Epi) of Age 1-5 Years - Noor , Mahal; Babar , Habibullah; Kiran , Wajeeha; Hussain , Muhammad; Ibrahim , Muhammad; Komal,; Kakar, Sana Ullah (Indus Journal of Bioscience Research, 2025)
Background: Vaccination is an important and economical way to lower mortality and prevent childhood illnesses. Even with the Expanded Program on Immunization (EPI) in place in Pakistan, a sizable fraction of kids still lacks adequate vaccinations. Objective: The objective of this study was to ascertain the prevalence of full vaccination among children between the ages of one and five as well as the main obstacles affecting vaccination uptake. Methods: A qualitative investigation was carried out at a Quetta tertiary care facility. 120 parents of children ages 1 to 5 were selected at random and interviewed using a semi-structured questionnaire. We gathered and thematically examined data on immunization status, EPI knowledge, and perceived difficulties. Findings: According to EPI criteria, only 56.7% of children received all recommended vaccinations. Lack of knowledge (72.5%), the distance to immunization facilities (51.7%), fear of adverse effects (37.5%), false information, and financial limitations were common obstacles. For about half of the caregivers, their main source of information was healthcare professionals. Conclusion: The results show that structural, educational, and cultural hurdles have resulted in notable discrepancies in vaccine coverage. To increase immunization rates, it is imperative to improve community-level engagement, service accessibility, and public health education.